Efficient Numerical Modelling of Extreme Wave - Tan , Vi Nie (Universiti Teknologi PETRONAS, 2020)
Ocean wave modelling has proven to be an important simulation tool in the offshore sector, whether the construction of offshore structure, transportation of natural resources or marine hydrodynamic activities require the prediction of wave behaviour. Due to this, OceanWave 3D model has gained popularity due to its availability and accuracy. The performance of the OceanWave 3D model under different wave cases had been identified to understand the efficiency of the model. The OceanWave 3D had obtain an optimal scaling where the output started to converge by employed multigrid to precondition a GMRES iterative solution. While exploring the model into more wave cases, the accuracy and efficiency of the simulation process is satisfaction. To obtain the largest wave that propagation among the wave groups, focus wave group that represent the largest wave that occur in the random sea was simulated using Ocean Wave 3D. It had validated against the other wave models, Multiple flux BEM model and Spectral model which had been highly validated by the quality experimental data and found to give accurate result. Future works will be carried out to study the parallelization of the algorithm to allow for larger problem size to be treated.